Produk Kewirausahaan "Jek's Parfume" - Iluh Nadila Rahma; Alvazaki Ikbar Maulana; Muhammad Yasin (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This assignment is compiled to fulfill the Entrepreneurship Application course which aims to equip students with basic skills in designing, developing, and implementing innovative and sustainable business ideas. In compiling this assignment, the author identifies business opportunities, designs business models, and analyzes the marketing, financial, and operational aspects of the chosen business idea. Through an applicative approach, this assignment also integrates entrepreneurship theory with field practice, so that it can improve students' understanding of the challenges and strategies in building a competitive business. The results of this assignment are expected to be the basis for students to develop a more structured and realistic startup business.